BEING UNSTUCK IN TIME: INTERPRETING THE DEICTIC SHIFT IN KURT VONNEGUT’S SLAUGHTERHOUSE FIVE - Sistiadinita (LPPM STBA Pontianak, 2018)
Going through the journey together, what makes the travel writing of Samuel Johnson differs with the biography of himself written by his travel-mate, James Boswell? One engrossing narrative; The Scarlet Letter has different voice of writing with another brilliant short story The Fall of the House of Usher despite the fact that they were written by two American writers around the same period (Nathaniel Hawthorne and Edgar Allan Poe). Each writing has different style from one person to another in a way that various perception is carved into distinct types of understandable language. In an early case, typical sense of language production and personal writing style do become crucial factors in constructing enriched and structured forms of literary works on any genre.Writing as a productive skill and an ideological exploration play a critical role for authors to express their language ability. Field of study to analyze language creation in literary works is called stylistics. Some texts in literary works can somehow affect reader’s thought or emotional feeling. This connection is related to the distance between the speaker and the reader, focusing on how a speaker transfers his language and in what way the reader grasps the textual meaning. Analyzing this special connection over time and space elements in stylistics is called deixis or deictic shift. Along with the idea, this essay will explore the deictic shift in Slaughterhouse Five or The Children’s Crusade.